Pengaruh Budaya Kaizen, Pelatihan Dan Komunikasi Terhadap Kinerja Karyawan (Studi Pada Kantor Kecamatan Arjasa Kab. Sumenep Jawa Timur) - Madra’ie Madra’ie; Abdul Kodir Djaelani; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe purpose of this study was used to determine how the influence of kaizen culture, training and communication on employee performance at the Arjasa District Office, Sumenep Regency, East Java. In this study, four variables are used, namely kaizen culture variables, training and communication which are independent variables, while employee performance is the dependent variable. Whereas in this study the number of respondents was 43 respondents. The data collection method is done by using a questionnaire. The analytical method used is multiple linear regression analysis. The results showed that the kaizen culture, training and communication simultaneously had an effect on employee performance. Kaizen culture partially affects employee performance, training partially affects employee performance, and communication partially affects employee performance. Keywords: Kaizen, Training, Communication, Employee Performance